Rethinking Unionism in a Changing World of Work, Family and Community Life - Pocock, Barbara (Relations industrielles / Industrial Relations, 2011)
This article considers the state of unionism today and argues that in strategizing for more workers’ power and effective worker representation, unions have – unsurprisingly – focussed upon the primary domain that workers occupy: the labour market and workplaces, applying a particular repertoire of tools. While social conditions beyond the terrain of work have always mattered and sometimes been recognized by activists and theorists, these are often under-attended in analysis and strategy. The article argues that the relevant social context includes the three “microsystems” of work, household and community life, their intersecting “mesosystems” and the larger “macrosystem” of labour law, social norms and gender cultures within which they are located. Together these construct a system which affects the ways in which unions can build power, the tools available to them, and the industrial issues that matter to workers. Significant changes in the three interacting domains of work, household and community life since the mid-1970s in many industrialized countries have changed the system within which workers’ create collective power. This is illustrated by evidence drawn from the Australian experience, and the changing forms and occupational structure of employment, and the changing shape of households and communities within which Australian workers live. Workers’ increasing mobility and work, family and community transitions make some of the traditional vehicles of union power outmoded – like collectivizing through a longstanding job or craft affiliation. Such changes call for new forms of collectivization and create new priorities for workers in their bargaining and industrial conditions. They also have implications for the tools – collective bargaining, substantive and procedural statutory rights or social security – that will most effectively improve workers’ circumstances.